2018
DOI: 10.1029/2018ja025391
|View full text |Cite
|
Sign up to set email alerts
|

Interchange Injections at Saturn: Statistical Survey of Energetic H+ Sudden Flux Intensifications

Abstract: We present a statistical study of interchange injections in Saturn's inner and middle magnetosphere focusing on the dependence of occurrence rate and properties on radial distance, partial pressure, and local time distribution. Events are evaluated from over the entirety of the Cassini mission's equatorial orbits between 2005 and 2016. We identified interchange events from CHarge Energy Mass Spectrometer (CHEMS) H + data using a trained and tested automated algorithm, which has been compared with manual event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
90
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(98 citation statements)
references
References 49 publications
8
90
0
Order By: Relevance
“…Roussos et al () found cases of high correlation between radiation belt and ring current variations, indicating the ring current is a key reservoir of the belt electrons through inward adiabatic heating (Kollmann et al, ; Paranicas et al, ). Adiabatic transport could be accomplished through stochastic magnetic field fluctuations (Roussos et al, ), centrifugal interchange instability injections (Azari et al, ; Paranicas et al, ; Rymer et al, ), or variable global scale convective flows (Roussos et al, ). Nonadiabatic mechanisms contributing to electron acceleration such as wave particle interactions (Horne et al, ) have been discussed by Woodfield Horne et al (, ) through numerical simulations and Cassini measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Roussos et al () found cases of high correlation between radiation belt and ring current variations, indicating the ring current is a key reservoir of the belt electrons through inward adiabatic heating (Kollmann et al, ; Paranicas et al, ). Adiabatic transport could be accomplished through stochastic magnetic field fluctuations (Roussos et al, ), centrifugal interchange instability injections (Azari et al, ; Paranicas et al, ; Rymer et al, ), or variable global scale convective flows (Roussos et al, ). Nonadiabatic mechanisms contributing to electron acceleration such as wave particle interactions (Horne et al, ) have been discussed by Woodfield Horne et al (, ) through numerical simulations and Cassini measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Often the final choice will depend on the application and problem specific details. For example, recent developments have discussed the use of skill scores for different solar and space physics applications (e.g., Bobra & Couvidat 2015) and their location on ROC diagrams (e.g., Manzato, 2007;Azari et al, 2018). A further detailed discussion on skill scores and their relation to ROC diagrams can be found within Manzato (2005).…”
Section: Introductionmentioning
confidence: 99%
“…Associated with the interchange process are injections of hot plasma from the middle into inner magnetosphere, which are often termed interchange injections. Interchange injections are typically characterized by an enhancement of energetic (>100 eV) plasma and a depletion of low‐energy plasma along with enhanced wave activity and magnetic field pressure (e.g., André et al, , ; Azari et al, ; Burch et al, ; Chen & Hill, ; Hill et al, ; Kennelly et al, ; Lai et al, ; Rymer et al, ). Within this very same spatial region in which interchange is occurring, modulations of the field and plasma conditions have been observed associated with rotational periodicities (e.g., Ramer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to the work by Kennelly et al (), several studies have evaluated interchange distributions at Saturn, extending to close to the end of the Cassini mission in mid‐September of 2017 (Azari et al, ; Lai et al, ). Azari et al () identified interchange injection events from 2005 to 2016 using a statistics‐based algorithm applied to H + flux intensitifications from the Magnetosphere Imaging Instrument's CHarge Energy Mass Spectrometer (CHEMS) (Krimigis et al, ). In their work, interchange injections were found to be both more prevalent and more intense between 7 and 9 R s .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation